2014
DOI: 10.14719/pst.2014.1.2.54
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability, Heritability and Genetic Advance in Mungbean (Vigna radiata L. Wilczek) Accessions

Abstract: The present study was conducted to assess the magnitude of genetic variability, heritability in broad sense and genetic advance among thirteen mung bean accessions for growth and grain yield characters. The study was conducted at the Haramaya University Rare research site and Hirna research site during the 2012/2013 cropping season. Randomized Complete Block Design with three replications was used for both locations. Each genotype was planted on a 1.2 X 2m plot consisting of four rows, which accommodates ten p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 11 publications
10
11
0
Order By: Relevance
“…This suggested the preponderance of additive gene action with low environmental influence for the determination of these characters and could be effective in phenotypic selection. Similar results were obtained by Hemavathy et al, (2015) for plant height, seed yield per plant and number of pods per plant, Pandey et al, (2007) for plant height, seed yield per plant and harvest index, Degefa et al, (2014) for seed yield per hectare and pods per plant, Rao et al, (2007) Singh et al, (2009) for days to 50% flowering and days to maturity. Contrary to this Rao et al, (2006) and reported high heritability and low genetic advance for days to maturity.…”
Section: Heritability and Genetic Advance Estimatessupporting
confidence: 71%
“…This suggested the preponderance of additive gene action with low environmental influence for the determination of these characters and could be effective in phenotypic selection. Similar results were obtained by Hemavathy et al, (2015) for plant height, seed yield per plant and number of pods per plant, Pandey et al, (2007) for plant height, seed yield per plant and harvest index, Degefa et al, (2014) for seed yield per hectare and pods per plant, Rao et al, (2007) Singh et al, (2009) for days to 50% flowering and days to maturity. Contrary to this Rao et al, (2006) and reported high heritability and low genetic advance for days to maturity.…”
Section: Heritability and Genetic Advance Estimatessupporting
confidence: 71%
“…The estimated data revealed that the PCV was higher than the GCV for all the studied traits which indicate that there was some environmental influence on these traits. These results were also line with the findings of Khajudparn and Tantasawat, 2011; Garg et al, 2017; Garje et al, 2013; Gadakh et al,, 2013; Kumar et al, 2013; Degefa et al, 2014 [21–26]. The lowest values of PCV and GCV in respective traits followed by the higher values, indicating these to be the lowest variable characters [27].…”
Section: Resultssupporting
confidence: 86%
“…The results exhibited moderate to high heritability (24.26%-99.19%) along with moderate genetic advances for the majority of the characters which offer to chances expected response to selection. The characters which exhibited high heritability indicates that the selection will be more effective whereas the traits showing low heritability indicates that the selection will be affected by the environmental factors [26]. The high heritability of a trait also indicated that this trait was control by the additive genetic effects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations